Strangers are friends I haven't met yet: a positive approach to young people's use of social media. (20th October 2016) - Wang, Victoria; Edwards, Simon
ABSRACT: This article reports on a recent research project undertaken in the UK that investigated young people's use of a range of prominent social media tools for socialising and relationship building. The research was conducted by a way of online survey. The findings suggest that this sample of British young people's socialising and relationship-building practices via the range of prominent social media tools reflect similar behavioural categories used offline. The use of these social media tools provides young people with an opportunity to manage, simultaneously, different categories of relationships in a multiplicity of 'spaces' created by these tools. The findings challenge the widely held belief that young people expose themselves to risk on social media as they indiscriminately befriend strangers. There is an absence of evidence of 'unjustified' intent to harm others. Indeed the findings indicate a strong desire to primarily support and protect those with whom relationships have been carefully established. The research suggests in fact that online engagement through social media can be positive and constructive for young people. It appears to provide them with a challenging 'space' to practice identity and relationship management strategies.